"Research progress in polymerization of conjugated dienes catalyzed by neodymium based catalysts" - YOU Jing-yu, GONG Di-rong (Hecheng xiangjiao gongye)
The microstructure of diene polymer was determined by catalytic systems in preparation of the polymer. Among numerous rare earth catalysts, neodymium based catalysts exhibited good activity and polymer yield in catalyzing conjugated dienes, and had high stereoselectivity, enabling the preparation of polymers with excellent properties. The performance of different types of neodymium based catalysts in diene polymerization, as well as the differences in the microstructure and molecular weight and their distribution of the products were reviewed with 45 references.